Enhancing Customer Satisfaction in Logistics Services: The Impact of Service Quality and Trust: Meningkatkan Kepuasan Pelanggan dalam Layanan Logistik: Dampak Kualitas Layanan dan Kepercayaan - Prastyorini, Juli; Mudayat , Mudayat; Ramadhan, Cahyo Alim (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to analyze the influence of service quality (X1) and trust (X2) on customer satisfaction (Y) at PT. Berkah Multi Cargo Logistics. The study adopts a descriptive quantitative approach, utilizing a total sampling method with 32 logistics service customers as respondents. Multiple linear regression analysis is employed to analyze the data. The results reveal a significant positive relationship between service quality (X1) and customer satisfaction (Y), as well as between trust (X2) and customer satisfaction (Y). Moreover, both service quality and trust demonstrate a significant positive impact on customer satisfaction. The coefficient of determination (R2) is calculated as 0.749, indicating that 74.9% of the variation in customer satisfaction can be explained by the combined influence of service quality and trust. This research employs survey methodology within a quantitative framework, employing both descriptive and inferential statistical analyses. The findings imply that enhancing service quality and fostering trust are pivotal in achieving customer satisfaction in the logistics services sector. These insights contribute to the body of knowledge in logistics management and offer practical implications for PT. Berkah Multi Cargo Logistics and similar industry professionals worldwide. Highlight: Service quality and trust significantly influence customer satisfaction in logistics services at PT. Berkah Multi Cargo Logistics. Service quality has a positive and significant impact on customer satisfaction in logistics services. Trust plays a crucial role in enhancing customer satisfaction in logistics services at PT. Berkah Multi Cargo Logistics. Keyword: Service Quality, Trust, Customer Satisfaction, Logistics Services, Quantitative Research